Isolation and Identification of Nitrogen-Fixing Rhizobacteria associated with Cocoa plantation (Theobroma cacao L) as Biofertilizer Agent - Nurul Afiyatul Jannah; Mustafa, Irfan; Jatmiko, Yoga Dwi (Graduate School, Universitas Brawijaya, 2022)
Ringinkembar Village, Sumbermanjing Wetan District, Malang Regency, is one of the centers for cocoa plantations using an organic farming system. However, over time this organic farming system experienced a decrease in fruit production, possibly from soil fertility and biofertilizers that were less available in the soil. This study aims to analyze the nitrogen-fixing ability and identify rhizosphere isolates that excel in nitrogen-fixing obtained from the rhizosphere of cacao (Theobroma cacao L) plant. Bacteria were isolated from the soil surrounding cocoa plant roots and grown on Nfb (Nitrogen free Bromothymol Blue) agar media. The nitrogen-fixing bacteria were analyzed with quantitative and qualitative methods. Six potential nitrogen-fixing isolates were identified based on the 16S rDNA sequence. The total number of isolates obtained from nitrogen-fixing isolation was six isolates. The R3.FN1 isolate showed the highest ammonia index at 0.52 µg.L-1 and was identified as Stenotrophomonas maltophilia KB13 with 99.87% similarity to the 16S rDNA sequence. Keywords: Cocoa, Nitrogen-fixing, Rhizosphere, Stenotrophomonas maltophilia.